Menelisik Persepsi Dosen PTKIN Tentang Gerakan Islam Radikal Di Indonesia - As’ad, Mahrus; Kurniasih, Siti (AL-ADYAN, 2023)
There is a crucial issue in several campuses namely the spread of radicalism and terrorism which has begun to target students on campus.The understanding is actually a simplification which results in the difficulty of capturing the substantive meaning of the two terms. The various perceptions of PTKIN lecturers about the meaning of "Islamic radicalism" made the Muslim public confused. This research was conducted to see the pattern of understanding of PTKIN Lampung lecturers regarding the phenomenon of Islamic Radicalism in Indonesia, the attitudes were developed by PTKIN Lampung lecturers facing the phenomenon of Islamic Radicalism in Indonesia, and the efforts were made by PTKIN Lampung lecturers in order to keep students away from the spread and threat of the Islamic radicalism on their campuses. This study involved 10 religious lecturers who worked at 2 PTKIN in Lampung as informants. This study adopted a qualitative investigative approach. This study investigates the participants as the sources of the data. The finding showed that the understanding or perception of PTKIN lecturers of the Lampung area about Islamic radicalism in Indonesia is not yet in one word (consensus). Most of them agree that the phenomenon of Islamic radicalism in Indonesia is a political movement that must be kept away from their students and the Muslim generation in general. But it seems that the necessity is simply because the approach used by the movement tends to emphasize the use of violence to achieve its political goals